Identifikasi Label Kode Pipa pada Sistem Konveyor untuk Pipe Handling Berbasis Template Matching - Imam Mulyono; Iman Fahruzi (ABEC Indonesia, 2022)
Nowadays, technological advancements are growing need for computer programs that might benefitindustrial purposes. Image recognition is crucial in technological advancements spanning from medical demandsto security and other industries. One of them is the necessity in the oil and gas industry for a computerapplication that can recognize pipe code labels, particularly in pipe handling. Because of the requirement forproduction assistance, to recognize the pipe code label image, an NI Vision control system was built. There arenumerous stages of label identification in this study, including taking photographs with a webcam camera(capture), cropping, grayscale, and saving data. The system can provide an accuracy of 88% based on test resultson 25 samples of ¾ inch PVC pipe code labels with a camera distance to the pipe code label field of 85 cm, 493color weights, and an optimal score level of 75%.